Development and preliminary results of an Electronic Medical Record (EMR)-integrated smartphone telemedicine program to deliver asthma care remotely. (May 2021) - Mammen, Jennifer R; Java, James J; Halterman, Jill; Berliant, Marc N; Crowley, Amber; Frey, Sean M; Reznik, Marina; Feldman, Jonathan M; Schoonmaker, Judith D; Arcoleo, Kimberly
Introduction: Technology-based interventions that can function within real-world practice and improve outcomes without increasing provider burden are needed, yet few successfully cross the research-to-practice divide. This paper describes the process of developing a clinically integrated smartphone-telemedicine program for adults with asthma and results from proof-of-concept testing. Methods: We used a contextually grounded intervention development approach and May's implementation theory to design the intervention, with emphasis on systems capabilities and stakeholder needs. The intervention incorporated symptom monitoring by smartphone, smartphone telemedicine visits and self-management training with a nurse, and clinical decision-support software, which provided automated calculations of asthma severity, control and step-wise therapy. Seven adults (aged 18–40 y) engaged in a 3-month beta-test. Asthma outcomes (control, quality of life, FEV1 ) and healthcare utilisation patterns were measured at baseline and end-of-study. Results: Each participant averaged four telemedicine visits (94% patient satisfaction). All participants had uncontrolled asthma at baseline; end-of-study 5/7 classified as well-controlled. Mean asthma control improved 1.55 points (CI = 0.59–2.51); quality of life improved 1.91 points (CI = 0.50–3.31), FEV1 percent predicted increased 14.86% (CI = −3.09–32.80): effect sizes of d  = 1.16, 1.09, and 0.96, respectively. Preventive healthcare utilisation increased significantly (1.86 visits/year vs. 0.28/year prior, CI 0.67–2.47) as did prescriptions for controller medications (9.29 prescriptions/year vs. 1.57 prescriptions/year, CI 4.85–10.58). Discussion: Smartphone telemedicine may be an effective means to improve outcomes and deliver asthma care remotely. However, careful attention to systems capabilities and stakeholder acceptability is needed to ensure successful integration with practice. Clinical Trials registration #: NCT03648203